What is cultural history? - Burke, Peter 1937- (What is history?, 2019)
"What is Cultural History? has established itself as an essential guide to what cultural historians do and how they do it. Now fully updated in its third edition, leading historian Peter Burke offers afresh his accessible guide to the past, present and future of cultural history across the globe"--Provided by publisher.